Molecular characterization of two glutathione peroxidase genes in Mytilus galloprovincialis and their transcriptional responses to sub-chronic arsenate and cadmium exposure - Q Wang; X Ning; Q Zhang; F Liu; H Wu; Y Zhang; J Zhao (Invertebrate Survival Journal, 2014)
Glutathione peroxidases (GPxs) are key enzymes in the antioxidant defense system of living organisms, and protect organisms against oxidative stresses. In this study, the full-length cDNA sequences encoding cytosolic GPx (MgcGPx) and phospholipid-hydroperoxide GPx (MgGPx4) were identified from Mytilus galloprovincialis. The mussels were exposed to 0, 1, 10, and 100 μg/L cadmium and arsenate for 30 days. The mRNA transcripts of these two genes and total GPx activity were examined in the gills and digestive gland after contaminants exposure. The mussels exposed to cadmium and arsenate responded mainly by down-regulating MgcGPx and MgGPx4 mRNA transcription in gills and up-regulating transcription in digestive gland. However, total GPx activities increased following cadmium exposure but decreased after arsenate stress in both tissues. These results suggest that MgcGPx and MgGPx4 perhaps play an important role in maintaining cellular redox homeostasis and protecting M. galloprovincialis against cadmium and arsenate toxicity. It can also be inferred that these genes have the potential to be used as molecular biomarkers for assessing cellular stress and toxicity of contaminants in this mussel.